Establishment of a novel experimental model for muscle‐invasive bladder cancer using a dog bladder cancer organoid culture - Elbadawy, Mohamed; Usui, Tatsuya; Mori, Takashi; Tsunedomi, Ryouichi; Hazama, Shoichi; Nabeta, Rina; Uchide, Tsuyoshi; Fukushima, Ryuji; Yoshida, Toshinori; Shibutani, Makoto; Tanaka, Takaharu; Masuda, Sosuke; et al. (Cancer science, 2019)
In human and dogs, bladder cancer (BC) is the most common neoplasm affecting the urinary tract. Dog BC resembles human muscle‐invasive BC in histopathological characteristics and gene expression profiles, and could be an important research model for this disease. Cancer patient‐derived organoid culture can recapitulate organ structures and maintains the gene expression profiles of original tumor tissues. In a previous study, we generated dog prostate cancer organoids using urine samples, however dog BC organoids had never been produced. Therefore we aimed to generate dog BC organoids using urine samples and check their histopathological characteristics, drug sensitivity, and gene expression profiles. Organoids from individual BC dogs were successfully generated, expressed urothelial cell markers (CK7, CK20, and UPK3A) and exhibited tumorigenesis in vivo. In a cell viability assay, the response to combined treatment with a range of anticancer drugs (cisplatin, vinblastine, gemcitabine or piroxicam) was markedly different in each BC organoid. In RNA‐sequencing analysis, expression levels of basal cell markers (CK5 and DSG3) and several novel genes (MMP28, CTSE, CNN3, TFPI2, COL17A1, and AGPAT4) were upregulated in BC organoids compared with normal bladder tissues or two‐dimensional (2D) BC cell lines. These established dog BC organoids might be a useful tool, not only to determine suitable chemotherapy for BC diseased dogs but also to identify novel biomarkers in human muscle‐invasive BC. In the present study, for the 1st time, dog BC organoids were generated and several specifically upregulated organoid genes were identified. Our data suggest that dog BC organoids might become a new tool to provide fresh insights into both dog BC therapy and diagnostic biomarkers. In the present study, we for the first time generated dog bladder cancer (BC) organoids and identified several genes specifically upregulated in the organoids. Our data suggest that dog BC organoids might become a new tool to provide new insights for both dog BC therapy and diagnostic markers.